Sex-Based Determination of the Perception of Femininity: Qualitative and Statistical Analyses - Lanovenko Iuliia; Yehorova Emma; Shkrebtiienko Liudmyla (Insight: the psychological dimensions of society, 2025)
The aim of this experimental study is to identify differences in the evaluation of femininity by individuals of different sexes, to determine specific criteria for assessing femininity, and to reveal the diversity in interpretations of feminine traits. Methods. The primary data collection method was a projective technique – an original set of stylized images representing femininity archetypes, created using the Lexica Art neural network service. Raw data were obtained through semi-structured interviews using these stylized archetypal images and a subjective scaling method. The study involved a sample of 33 individuals aged 20 to 65, with an approximately equal number of men and women. The collected data were analyzed using content analysis (which allowed for identifying additional criteria for the perception of femininity, significantly expanding the information found in the literature and enriching the semantic depth of feminine images) and statistical analysis (including frequency distribution, Mann–Whitney U test, cross-tabulation, and analysis of variance). Results. Statistically significant differences were found in the evaluation of femininity criteria between men and women. The traits of “maturity” (rated more highly and valued more by women) and “modesty” (more often emphasized by men) showed statistically significant differences. The archetypal image of the “Berehynia” (Guardian or Keeper) was perceived as the most feminine by men and the least feminine by women. Discussion and Conclusions. The study confirms that widely accepted qualities in evaluating femininity (e.g., beauty) remain relevant for both sexes. Among the additional criteria identified, the traits that most influence the perception of a woman as feminine include confidence, maturity, wisdom, self-sufficiency, modesty, and inner richness. A notable contribution of this work is the trial use of stylized archetypal images of femininity, which opens the possibility of developing metaphorical cards titled “Archetypes of Femininity” in the future. Even at this stage, the image set has demonstrated therapeutic potential.